DOOMSCROLLING SEBAGAI PREDIKTOR GEJALA DEPRESI PADA REMAJA SMA: STUDI CROSS-SECTIONAL DI DEPOK DAN BOGOR - Dian Fitri; Rochmawati Rochmawati (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Doomscrolling, defined as the compulsive habit of repeatedly consuming negative information content on social media, is hypothesized to contribute to increased depressive symptoms among adolescents. The purpose of this research was to examine whether or whether senior high school students in Bogor and Depok were more likely to exhibit depressive symptoms if they engaged in doomscrolling. One hundred twenty-three students were chosen at random from a cluster for this cross-sectional study. The Doomscrolling Scale was used for measuring doomscrolling, and the Patient Health Questionnaire-Adolescents for measuring depressed symptoms. The main analysis in this study was binary logistic regression. Results showed that 45.5% of respondents experienced moderate-to-severe depressive symptoms. Doomscrolling was a significant predictor of depressive symptoms after controlling for confounders (OR = 1.04; 95% CI = 1.01–1.06; p = 0.003), with the model explaining 29.8% of the variance. Social media use duration of more than 3 hours per day was also a significant predictor (OR = 2.15; p = 0.039). Doomscrolling is a measurable risk factor that should be integrated into mental health assessment and intervention programs for adolescents in school settings. ABSTRAK Perilaku doomscrolling, yakni kebiasaan kompulsif mengonsumsi konten informasi negatif secara berulang di media sosial, diduga berkontribusi terhadap peningkatan gejala depresi pada remaja. Penelitian ini bertujuan menganalisis peran prediktif doomscrolling terhadap gejala depresi pada siswa SMA di Kota Depok dan Kabupaten Bogor. Desain cross-sectional analitik digunakan dengan melibatkan 123 siswa yang dipilih melalui cluster random sampling. Pengukuran doomscrolling menggunakan Doomscrolling Scale dan gejala depresi menggunakan Patient Health Questionnaire-Adolescents, dengan analisis utama menggunakan regresi logistik biner. Hasil menunjukkan bahwa 45,5% responden mengalami gejala depresi sedang-berat dan rata-rata skor doomscrolling berada pada kategori sedang. Doomscrolling terbukti sebagai prediktor signifikan gejala depresi setelah dikontrol variabel konfounding (OR = 1,04; CI 95% = 1,01–1,06; p = 0,003), dengan model menjelaskan 29,8% variasi gejala depresi. Durasi penggunaan media sosial lebih dari 3 jam per hari juga merupakan prediktor signifikan (OR = 2,15; p = 0,039). Doomscrolling merupakan faktor risiko terukur yang perlu diintegrasikan dalam asesmen dan intervensi kesehatan mental remaja di sekolah.